An investigation into adverbs and adverbial phrases expressing time in English versus Vietnamese - a cognitive semantic perspective - Ngo, Thi My Dung.; Tran Quang Hai, Ph.D. (Đà Nẵng : The University of Da Nang, 2012)
Introduction; Literature review and theoretical background; Methods and procedures...
Master thesis in the English language. Field: The English language. Code: 60.22.15.
Keywords: English language; English language -- Adverb; English language -- Adverbial phrases; English language -- Semantic